2019
DOI: 10.1074/jbc.ra119.008732
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of long noncoding RNA (lncRNA)-chromatin interactions reveals lncRNA functions dependent on binding diverse regulatory elements

Abstract: Edited by Joel M. GottesfeldOver the past decade, thousands of long noncoding RNAs (lncRNAs) have been identified, many of which play crucial roles in normal physiology and human disease. LncRNAs can interact with chromatin and then recruit protein complexes to remodel chromatin states, thus regulating gene expression. However, how lncRNA-chromatin interactions contribute to their biological functions is largely unknown. Here, we collected and constructed an atlas of 188,647 lncRNA-chromatin interactions in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 66 publications
(64 reference statements)
1
21
0
Order By: Relevance
“…The function of lncRNAs is similar to that of miRNAs, which are able to regulate the expression of neighboring target genes (36,37). The present study indicated that certain lncRNAs are significantly associated with their target genes and that those lncRNAs exert their function through their predicted target genes.…”
Section: Discussionsupporting
confidence: 51%
“…The function of lncRNAs is similar to that of miRNAs, which are able to regulate the expression of neighboring target genes (36,37). The present study indicated that certain lncRNAs are significantly associated with their target genes and that those lncRNAs exert their function through their predicted target genes.…”
Section: Discussionsupporting
confidence: 51%
“…Subsequently, these miRNAs lose the ability to function as a tumor suppressor and oncogenic mRNAs are translated contributing to tumorigenesis [63]. Moreover, as several lncRNAs, which exert their functions by binding to both promoter and distal regulatory elements, NEAT1 controls 13.3% of genes in the PI3K-AKT signaling pathway by interacting with distal regulatory elements [64].…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 has been shown to promote tumorigenesis in several different cancers by regulating the function of several tumor suppressor miRNAs ( Prinz et al, 2019 ). NEAT1 has also been shown to regulate proliferation and fibrosis of mesangial cells, which are specialized cells in the kidney that make up mesangium of glomerulus, in diabetic nephrophathy by activating AKT/mTOR pathway ( Huang et al, 2019 ; Zhang et al, 2019 ). The physiological consequence of this regulation in cellular hypertrophy remains unclear.…”
Section: Introductionmentioning
confidence: 99%